FAKTOR RISIKO KEGEMUKAN PADA ANAK SEKOLAH USIA 6-18 TAHUN DI DKI JAKARTA - Sri Prihatini; Abas Basuni Jahari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2007)
ABSTRACT Background: The result of nutritional status surveys on school age children in 10 big cities in Indonesia in 2005 showed that the prevalence of obesity in school age children in DKI Jakarta was the highest with percentage of 6 % compared to other big cities that only under 3%. Further analysis was conducted to examine the risk factor related to obesity in school age children in DKI Jakarta. Objectives: Data analysis was done to study the risk factor related to obesity in school age children in Jakarta.Material and Methods: Experimental design was cross sectional. Samples were primary school, junior high school and senior high school students age 6 – 18 years old in five regions of DKI Jakarta. The number of total samples was 7195 students. Data collected were anthropometry, social-economy, food consumption pattern, physical activities, and life style. Nutrition Status was determined by calculating Body Mass Index (BMI) using CDC 2000 reference. Results: The prevalence of overweight student in DKI Jakarta was 6%. The prevalence of malnutrition and severe malnutrition students were 11,2% and 1,2% respectively. The group of student ≤9 years old had the highest prevalence of obesity and severe malnutrition. The prevalence was more in male students than female. The education level of parents, often consumes an oily snacks, like to buy a deep fry snacks, oily snacks, often consume supplement, and rarely do household work have strong relation with obesity (p<0,05). Conclusion: Male students age ≤9 year old have higher risk of obesity and malnutrition than female students.  The education level of parents, often consumes an oily snacks, like to buy a deep fry snacks, oily snacks, often consume supplement, and rarely do physical work are risk factors of obesity in school age children. [Penel Gizi Makan 2007, 30(1): 31-39]   Keywords: Body Mass Indeks (BMI), Nutrional Status, Obesity risk